Web 2.0 Technologies: Disruptive or Liberating for Adult Education? - Rita Kop (Adult Education Research Conference, 2008)
Adult educators have been reluctant to engage with the latest second generation Internet technologies. New ideas on how these technologies could reform the structure and processes of adult education are examined in relation to Illich’s educational vision from the 1970s.
Keywords: technology; change